PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III PADA MATA PELAJARAN MATEMATIKA DI SD NEGERI 1 SRIMULYA JAYA - Nurliana, Ika; Khoiriyah, Binti; Pixyoriza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning outcomes for Grade 3 students at SD Negeri 1 Sri Mulya Jaya remain low due to several factors, primarily the fact that teachers have not yet implemented learning models that actively engage students. The learning process remains teacher-centered, with the teacher dominating activities through the delivery of material and practice exercises. Consequently, teachers are required to implement more innovative, student-centered learning approaches. One such approach is the implementation of the